Building a Just Law: The Role of Legal Professional Ethics in Indonesia - Muhammad Syahrul Muttaiqen; Ahmad Yubaidi; Muhammad Husni Abdulah Pakarti; Husain Husain; Abdulmajeed Bolade Hassan Bello (Universitas Muhammadiyah Bandung, 2025)
The professionalism of a legal profession is not only due to being capable, intellectual, and successful in their field as law enforcement officers, but the behavioral aspect is also part of the assessment that must be owned in implementing the Code of Ethics or Legal Professional Ethics to uphold law and justice. However, if we look at the reality, there are still many legal practitioners who have not complied with the Legal Professional Code of Ethics. The research method in this journal uses juridical-normative, which uses literature-based secondary data sources. The results of this study are that the Legal Professional Code of Ethics must be obeyed (compelling) even though it is not officially made into regulations. Because Legal Professional Ethics has an important role in law enforcement which is also a manifestation of efforts to realize better law.